Fishermen’s Family Perceptions on Economic Uncertainty and Social Challenges: Persepsi Keluarga Nelayan tentang Ketidakpastian Ekonomi dan Tantangan Sosial - Wahadi, Wahadi; Yana, Enceng; Rusdiyana, Rusdiyana (Indonesian Journal of Innovation Studies, 2025)
General Background: Coastal communities in Indonesia depend heavily on fisheries, with fishermen playing crucial roles in both resource provision and economic vitality. Specific Background: In Kejawanan Beach, Cirebon, fishing is the main livelihood despite its inherent uncertainties. Knowledge Gap: While many studies address coastal livelihood issues, few explore the integrated perceptions of fishing families regarding both economic and social impacts in this region. Aims: This study aims to understand how fishing families in Kejawanan perceive the socio-economic effects of the fishing profession and the factors shaping those perceptions. Results: Using a qualitative method with thematic analysis, the study revealed three major themes: unstable income tied to fishing seasons, social pressures including emotional strain and limited family interaction, and adaptive survival strategies like borrowing or saving. Novelty: This study presents a holistic analysis of household-level perceptions, combining economic instability and social dynamics within a single framework, which is rarely addressed in similar coastal studies. Implications: Findings highlight the urgency for inclusive financial innovations (e.g., digital cooperatives), gender-aware economic planning, and educational support to break the poverty cycle among fishing families, informing more effective coastal development policies.Highlight : Unstable Earnings: Fishermen’s income depends heavily on seasons and daily catch results. Social Impact on Families: Limited family time and the double burden on women are key concerns. Survival Strategies: Families cope by saving during harvest seasons and borrowing during lean periods Keywords : Fishermen, Fluctuation, Income, Social, Kejawanan